2023
DOI: 10.3390/microorganisms11040870
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Pathway Exploration of the Epidermidibacterium keratini EPI-7T

Abstract: Functional cosmetics industries using skin microbiome screening and beneficial materials isolated from key microorganisms are receiving increasing attention. Since Epidermidibacterium keratini EPI-7T was first discovered in human skin, previous studies have confirmed that it can produce a new pyrimidine compound, 1,1′-biuracil, having anti-aging effects on human skin. Therefore, we conducted genomic analyses to judge the use value of E. keratini EPI-7T and provide up-to-date information. Whole-genome sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Previous studies reported that spermine production by microbiota in the intestines was six times higher than that produced from dietary intake, 19 and spermine in the vagina is believed to be produced by the vaginal microbiota. Orotic acid is produced by the microbiota 20 and was decreased in samples taken at the time of embryo transfer. The reduced metabolism of orotic acid in the pregnant group suggests either fewer relevant microbes or decreased activity of microbes in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that spermine production by microbiota in the intestines was six times higher than that produced from dietary intake, 19 and spermine in the vagina is believed to be produced by the vaginal microbiota. Orotic acid is produced by the microbiota 20 and was decreased in samples taken at the time of embryo transfer. The reduced metabolism of orotic acid in the pregnant group suggests either fewer relevant microbes or decreased activity of microbes in this group.…”
Section: Discussionmentioning
confidence: 99%